Billy's Drum: Feet and Rhythm in Sesame Therapeutic Practice. Issue 2 (July 2018) - Butler, Catherine
Billy Lindkvist's demonstration at a Sesame Seasonal School of foot and rhythm work for connection, sense of self, and grounding, was an inspiration for me to train as a Sesame practitioner. In this paper, I will explore the origins of this work in Billy's experience and how she developed it, how it has continued in Sesame training, and lastly show how I have used this associated aspect of a basic strand of the Sesame Approach, Movement with Touch and Sound, from RCSSD placements through to current client work, describing its application and adaptation for different client groups including people with dementia, ASD, Parkinson's, and physical and learning difficulties.